Zagadnienia etyczne w wystąpieniach awangardowych - Stangret , Paweł (Colloquia Litteraria, 2024)
The article is focused on ethical issues of avant-garde. It’s important especially for creation ex nihilo, which redefined ontology of work of art. Modern artists didn’t limit only for aesthetic, but they want to create whole cultural project. Characteristic for modern art is complex of diagnosis (of crisis of culture), reaction for new reality and project of future culture. The same is for ethical issues. In the same time: rebellion for culture and it’s collapse and creating the new way of ethic – in work of art and in culture. That’s why the article is focused on literary text and commentaries. These problems was overlooked in reading of avant-garde creation.